STUDY ON EFFECT OF QUADRICEPS MUSCLE RESISTANCE TRAINING ON CARDIORESPIRATORY PARAMETERS IN YOUNG HEALTHY FEMALES - KALE, SUDEEP; Y MANDSAURWALA, MUNIRA; DEO, MEDHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objectives of the study were to determine and compare acute changes in the cardiorespiratory parameters in young, healthy females in response to 3 weeks resistive exercises to quadriceps muscle using DeLorme’s and MacQueen’s protocol. Methods: The study was carried in 30 young, healthy females aged 18–25 years. Resting blood pressure measured in systole blood pressure (SBP), blood pressure measured in diastole diastolic blood pressure (DBP), respiratory rate (RR), and heart rate (HR) were measured. Subjects were then divided randomly into two groups containing 15 subjects in each group. Ten repetition maximum was measured for each subject. Group A subjects were given resistive exercises for the quadriceps muscle bilaterally using DeLorme’s protocol and Group B subjects were given training with MacQueen’s protocol. In both groups, training was given thrice a week for 3 weeks. Results: SBP, HR, and RR showed significant statistical differences after 3 weeks of PRE using DeLorme’s protocol; however, DBP changes were non-significant. SBP, HR, RR, and DBP showed significant statistical difference after 3 weeks of PRE using MacQueen’s protocol. In a comparison of DeLorme’s protocol and MacQueen’s protocol, a significant statistical difference in parameters of SBP and HR was observed. Improvement was more in subjects trained with MacQueen’s protocol. Conclusion: The resistive training has beneficial effects on HR, systolic SBP, and RR. MacQueen protocol is more effective than DeLorme’s protocol. Hence, resistive training should be included in an exercise program.